Kalam Suruhan Surah Al-Baqarah (KALAM)”Android Application:21st Century M-Learning Medium in Islamic Science - Sharifah Norshah Bani, Syed Bidin; Syadiah Nor, Wan Shamsuddin; Nuril Ham Al Hafizah, Zaharia (2017)
The rapid development of information and communication technology (ICT) today has led to changes in the teaching and learning patterns in the education sector. Mobile learning (m-learning) which is self-learning education that is based on mobile technology as an educational tool is gaining momentum among teachers and students. An app that is accessible through mobile technology are booming with the advent of a variety of apps including Islamic science apps. This study is to introduce an android app named Kalam Suruhan Surah Al-Baqarah (KALAM). This app is about Al-Qur’an interpretation of commandment verses in Chapter Al-Baqarah related to six chapters, namely Faith (Akidah), Worship (Ibadah), Property (Harta), Honor (Munakahat), Manners and Food (Adab dan Makanan) and Jihad and Crime (Jihad dan Jenayah). It aims to provide exposure on its function and usefulness as the 21st century m-learning medium in Islamic sciences, especially in the field of Al-Qur’an interpretation. The study of this app is also expected to give benefit and ideas to the other researchers in developing more Islamic science apps in order to ensure the Islamic knowledge is on the rise as well as the other field.